Analisis Beban Kerja Fisik Menggunakan Metode Cardiovaskular Load dan Konsumsi Energi pada Karyawan Pemadam Kebakaran di PT X - Zaini, Mohammad; Dira Ernawati (Jurnal Serambi Engineering, 2025)
The high physical workload of firefighters has the potential to cause fatigue and reduce performance, compromising safety and productivity. Given the importance of accurate measurement of physical workload, the aim of this study was to analyse physical workload using the Cardiovascular Load (CVL) method and energy expenditure to assess the level of physical intensity exerted by the body during work activities among firefighters using direct observation and pulse measurement during the working day, and estimation of energy expenditure based on recorded physical activity. The research results show that the physical workload of the employees is rather low, with an average CVL of 22.3%, indicating that there is no classification of fatigue. Energy consumption also has an average energy consumption value of 1.51, which shows that their energy consumption is in the light category. On the basis of the results of this analysis, PT also carries out regular health monitoring of physical conditions with the aim of keeping employees in optimal condition. It is hoped that this research will provide a basis for companies to develop policies to manage the physical workload of firefighters.